2009
DOI: 10.1016/j.jacc.2008.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Thrombus Aspiration During Primary Percutaneous Coronary Intervention Improves Myocardial Reperfusion and Reduces Infarct Size

Abstract: Thrombectomy prevents thrombus embolization and preserves microvascular integrity reducing infarct size, and it therefore represents an useful adjunctive therapy in PPCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 329 publications
(70 citation statements)
references
References 17 publications
7
61
0
Order By: Relevance
“…The randomized clinical trial (RCT) TAPAS, in particular, showed that manual thrombus aspiration (TA) improved myocardial reperfusion and reduced mortality in STEMI patients at 1-year follow-up [5,6] . These results, confirmed by other studies [7][8][9][10] , including a meta-analysis [11] of 11321 patients from 20 RCT showing lower rates of late mortality, reinfarction and stent thrombosis in patients underwent manual TA compared with conventional primary PCI, led to a recommendation class Ⅱa for manual TA in patients undergoing primary PCI for STEMI [12] . Nevertheless, the use of the thrombectomy devices is still controversial and not routine in STEMI patients, especially because some studies have shown no impact on clinical outcome [13][14][15][16][17][18][19][20] , such as the TASTE trial [21] .…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…The randomized clinical trial (RCT) TAPAS, in particular, showed that manual thrombus aspiration (TA) improved myocardial reperfusion and reduced mortality in STEMI patients at 1-year follow-up [5,6] . These results, confirmed by other studies [7][8][9][10] , including a meta-analysis [11] of 11321 patients from 20 RCT showing lower rates of late mortality, reinfarction and stent thrombosis in patients underwent manual TA compared with conventional primary PCI, led to a recommendation class Ⅱa for manual TA in patients undergoing primary PCI for STEMI [12] . Nevertheless, the use of the thrombectomy devices is still controversial and not routine in STEMI patients, especially because some studies have shown no impact on clinical outcome [13][14][15][16][17][18][19][20] , such as the TASTE trial [21] .…”
Section: Introductionsupporting
confidence: 72%
“…tween patients treated with or without TA [6,7,10,20,28] except for one brief work [29] that demonstrated a higher stent diameter after manual TA, in STEMI patients treated with bare metal stents. Recently, the TASTE trial [21] also showed the need for fewer stents per procedure in manual TA group in comparison with conventional PCI.…”
Section: Fernández-rodríguez D Et Al Thrombus Aspiration Optimizes mentioning
confidence: 99%
“…Various thrombectomy devices have been developed allowing manual or mechanical removal of intracoronary thrombi. All thrombectomy devices have shown benefits compared with conventional PPCI, when surrogate endpoints, such as angiographic flow assessment, LVEF assessment, infarct size reduction by perfusion imaging, enzymatic analysis and ST-segment resolution were used [26,29,[73][74][75][76][77][78][79] . To date evidences about hard endpoints from randomized controlled trials, comparing manual and mechanical thrombectomy, are limited and even conflicting.…”
Section: Thrombectomy Devicesmentioning
confidence: 99%
“…The EXPIRA trial, evaluating the Export catheter (Medtronic, Inc, Minneapolis, MN) in PPCI, demonstrated improvement in surrogate markers, including myocardial blush grade and ST-segment resolution [78] . The TAPAS trial is the largest randomized trial to date evaluating thrombus aspiration in PPCI for STEMI [26] .…”
Section: Thrombectomy Devicesmentioning
confidence: 99%
“…EXPIRA trial [11] was done to evaluate the impact on myocardial perfusion and infarct size as assessed by contrastenhanced magnetic resonance imaging of a manual thrombectomy device, Export Medtronic (EM), as adjunctive therapy in primary percutaneous coronary intervention in a subset of patients with anterior ST-segment elevation myocardial infarction. The results showed that; Myocardial blush grade 2 occurred more frequently in the aspiration group (88%) vs. (60%) in the conventional PCI group and the difference was highly statistically significant (p=0.001) [11].…”
Section: Discussionmentioning
confidence: 99%